Hematological Markers to Predict Enterectomy Versus Enterotomy in Dogs with Foreign-Body Intestinal Obstruction: Preliminary Data - Lorena Espadas González; Eva M. Pérez-Merino; Irene Cantalejo Rodrigo; Jesús M. Usón-Casaús; Nieves Pastor Sirvent (Animals)
Intestinal obstruction caused by a foreign body accounts for 80% of all canine intestinal blockages [...]